Implantable Electroceutical Approach Improves Myelination by Restoring Membrane Integrity in a Mouse Model of Peripheral Demyelinating Neuropathy (Adv. Sci. 32/2022). Issue 32 (14th November 2022) - Intisar, Aseer; Shin, Hyun Young; Kim, Woon‐Hae; Kang, Hyun Gyu; Kim, Min Young; Kim, Yu Seon; Cho, Youngjun; Mo, Yun Jeoung; Lim, Heejin; Lee, Sanghoon; Lu, Q. Richard; Lee, Yun‐Il; et al.
Abstract : Charcot‐Marie‐Tooth Disease Charcot‐Marie‐Tooth (CMT) disease – the most prevalent inherited peripheral neuropathy worldwide – currently lacks an approved treatment, as the biochemical interventions attempted have remained unsuccessful. In article number 2201358, Minseok S. Kim and co‐workers introduce a paradigm‐shifting biophysical treatment for CMT disease based on electroceuticals. The optimal electrical stimulation condition improves peripheral myelination by inducing a dynamic recovery in the distribution of key biomolecular constituents of myelin, thus restoring the myelin membrane integrity.